A Village Greater than the World: Acceptance Speech for the 2021 Newman Prize for Chinese Literature. (2nd January 2021) - Yan, Lianke; Abrahamsen, Eric
Abstract : In Yan Lianke's works, the village is always a microcosm of China's history. In Yan's acceptance speech of the 2021 Newman Prize for Chinese Literature, he declares that the village of his homeland is truly all of China entire, and even greater than the world. All the possibilities of humanity exist inside that village. As a writer, he is committed to discovering the connections between the village and the rest of the human world in his literature.